2004
DOI: 10.1007/s11746-004-0903-x
|View full text |Cite
|
Sign up to set email alerts
|

How is chemical interesterification initiated: Nucleophilic substitution or α‐proton abstraction?

Abstract: Esters of carboxylic acids including 2-methylhexanoic, 2-methylbutyric, 2,2-dimethyl-4-pentenoic, palmitic, and oleic acids were tested as substrates in methoxide-catalyzed interesterification and transesterification. The aliphatic acid esters participated in the ester-ester interchange upon addition of catalytic sodium methoxide. Their isopropyl esters also produced methyl esters on heating with sodium methoxide. The esters of α-methyl-substituted acids did not participate in the ester-ester interchange. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 8 publications
0
21
0
3
Order By: Relevance
“…logo, a reação é randômica e entropicamente dirigida até que o equilíbrio termodinâmico seja alcançado. 5,6 Embora existam diversos estudos sobre o mecanismo da interesterificação química e produtos interesterificados, a cinética da reação ainda é pouco explorada na literatura. 7 Neste sentido, apenas a temperatura de reação se revela como parâmetro praticamente consolidado.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…logo, a reação é randômica e entropicamente dirigida até que o equilíbrio termodinâmico seja alcançado. 5,6 Embora existam diversos estudos sobre o mecanismo da interesterificação química e produtos interesterificados, a cinética da reação ainda é pouco explorada na literatura. 7 Neste sentido, apenas a temperatura de reação se revela como parâmetro praticamente consolidado.…”
Section: Introductionunclassified
“…Contudo, com a diminuição desse tempo de reação haveria, conseqüentemente, diminuição de custo do processo e melhor aproveitamento da capacidade dos reatores, além de diminuir a probabilidade de formação de sabões, principal subproduto da reação. 5,10,11 Ainda, a importância de um estudo minucioso do tempo de reação reside no fato de que a intensidade de formação de novas espécies triacilglicerólicas pode afetar consideravelmente as propriedades físicas das bases oleosas. 12 gorduras parcialmente interesterificadas apresentam teor de sólidos, composição triacliglicerólica e comportamento de cristalização que diferem substancialmente da mistura inicial e do produto completamente randomizado.…”
Section: Introductionunclassified
“…Besides the observation by Liu [13] that without an a-hydrogen, there is no ester interchange, which observation cannot be explained by the glycerolate mechanism, further objections against the glycerolate mechanism were put forward [14]: it does not explain why an amount of soap or FFA is formed that is equivalent to the amount of sodium methanolate catalyst used, and it does not explain why compounds like acetone [15] or "an aprotic substance selected from the group consisting of dimethyl formamide, dimethyl acetamide, dimethyl sulphoxide, dimethyl cyanaminde, 3,3-dimethylaminopropionitrile, and mixtures thereof" [16] accelerate the ester interchange reaction. According to Seestrom et al [17] an equivalent amount of soap or FFA is formed during interesterification according to: 2 triglycerides + 1 sodium methoxide → 1 soap + 1 methyl esters + 2 diglycerides This observation has been confirmed independently by several authors and also forms the basis of cost comparisons [18, p. 155].…”
Section: The "Enolate" Mechanismmentioning
confidence: 91%
“…In 2004, Liu [13] asked how the chemical interesterification is initiated: by a nucleophilic substitution or by the abstraction of an a-proton? By observing that a-substituted fatty acids did not participate in ester-ester interchange on the addition of sodium methanolate and only formed methyl esters on the subsequent addition of methanol, Liu [13] concluded that the first step in the methanolate catalysed interesterification is the abstraction of an a-hydrogen from a fatty acid moiety to form an enolate carbanion.…”
Section: Formation Of An Enolate Anionmentioning
confidence: 99%
See 1 more Smart Citation